Dr. Mirta Widia Enhances Ergonomic Risk Assessment Efficiency through the I-ERA System - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 1 September 2023 - Every day, there is an increase in occupational diseases recorded by the Social Security Organization (SOCSO) in Malaysia.